4th TCMTs 2025 - Book of Abstracts - Conference Scientific Committee (AlQalam Journal of Medical and Applied Sciences, 2025)
The 4th Tripoli Conference on Medical Technologies was held on Saturday, November 22, 2025, at the Faculty of Medical Technology, University of Tripoli. It is a specialized scientific platform focusing on artificial intelligence and digital transformation in healthcare, bringing together academics, researchers, and graduate students to explore cutting-edge innovations.